Germination of Phyllanthus urinaria as influenced by media, environment and branch position - Wong, Ying Yong (2015)
Phyllanthus urinaria or ‘Pokok Dukung Anak’ is a common weed which can be found in cultivated land as well as abandoned area. This plant also serves as traditional herbs in many parts of the world to treat malaria, asthma, hepatitis and other diseases. The main propagation method of P. urinaria is through seeds, however it has been reported that the germination is low. Therefore, in this study, the seeds of P. amarus were grown to maturity and the naturally dehisced seed were harvested. In the first experiment, the seeds were treated with 5 different growing media in combination with 3 different environments in order to obtain high germination in P. urinaria. In the second experiment, the seeds were grown under the structured house and the seeds were harvested on 13 day after anthesis from main stem and first branch for germination improvement. The treatments were considered as two factorials. The seeds were subjected to germination test and monitored for 28 days. The experimental design used was be RCBD. The data was collected every day. The best result obtained from experiment one treatment M2E2 – 50% peat with 50% perlite under structured house. The germination percentage was as high as 85% with mean daily germination which was about 1.7 seeds/ day. The vigor index was 727.70. For experiment two, the best result was obtained in treatment M2B1 – 50% peat with 50% perlite peat where the seeds were harvested from first branch. The germination percentage was 81.7% with mean daily germination which was about 1.7 seeds/ day. The treatment has the highest vigor index (571.67) among the treatments. For better germination in P. urinaria, the recommended media to be used was 50% peat with 50% perlite under structured house. Also, seeds harvested from first branch will give better germination.